Bank efficiency and non-performing loans in Namibia: a two-stage DEA bootstrapping approach - Haixuna, Joyce (Graduate School of Business (GSB), 2024)
In the banking industry, non-performing loans are an undesirable by-product of producing loans and may lead to inefficiency. Therefore, it is important that NPLs are accounted for in the analysis of the efficiency of banks. This paper investigated the relationship between non-performing loans and bank efficiency in Namibia by using a two-stage approach, which was applied on quarterly data spanning the period 2010Q1 to 2020Q4. In the first stage, the Data Envelopment Analysis technique was employed to estimate efficiency scores of the eight commercial banks in Namibia, with and without non-performing loans as an undesirable output variable. The efficiency scores obtained in the first stage were then used in the second stage truncated bootstrapped regression model to determine the effect of non-performing loans on bank efficiency. The study found that there was low variability in the technical efficiency scores of the Namibian banking industry for the study period, where the trend was unevenly constant with a slight drop after 2016. Furthermore, the results indicated that leaving out non-performing loans as an output variable leads to the under-estimation of the efficiency results. From the second-stage regression results, the study found a negative significant relationship between bank efficiency and non-performing loans, which indicated that an increase in non-performing loans decreases bank efficiency. This signifies the role that credit risk management plays on the efficiency and stability of banks, in which case should be closely monitored. The result also confirmed the bad management hypothesis, as proposed by Berger and DeYoung (1992), which highlights that a lack of efficiency in management of banking institutions will result in bad loan quality. The study also identified bank size, ROA and overhead costs as other significant determinants of efficiency. From a strategic standpoint, the study suggests that the Namibian banking industry invest in systems and processes that are technologically efficient to enhance efficiency, seeing that the study observed a considerable amount of inefficiency on average, for the study period.